International commercial arbitration landmark decisions of French arbitration law - Le Bars, Benoit (LexisNexis, 2019)
La 4ème de couv. indique : "French trained lawyers are familiar with collections of important decisions, so-called grands arrêts, in different areas of law. While this might come as a surprise to many common lawyers, there is indeed an important focus on case law in many areas of civil law, such as private international law, arbitration, etc. A first edition of this book was published in French in 2016. However, this new edition is not a translation only : since the original French edition was published, a number of landmark decisions, internationnally commented, have introduced noteworthy topics. We also added a new analysis of the adjudicative powers of arbitral tribunals that didn't appear in the first edition, to set out all the functions that arbitral tribunals may perform and that make arbitrators (dis)similar to national judges. Derived from centuries of developments, the principes guiding all arbitration cases permeate each of our actions, as counsel or arbitrator.
Traduction enrichie de nouveaux commentaires d'un ouvrage paru en français en 2016 intitulé "Arbitrage commercial international : les grands arrêts du droit français"
Keywords: Arbitrage (droit); Arbitrage commercial international